Exploring EFL Teacher’s Motivational Regulation in the Demotivating Environment A Case Study in Indonesia - Adyta, Yafi Dwika; Kuncahyo, Nanda Lintang Utari; Makhsunah, Urfatul; Salam, Hamidah (IJET (Indonesian Journal of English Teaching), 2024)
Although extensive research has been carried out on learners’ demotivation, there is limited research exploring the demotivating factors of teachers, especially in Indonesia. Heavy workloads and challenging classroom environments can lead to decreased teacher motivation, which can affect students’ academic achievement. Therefore, it is pivotal for teachers to regulate their motivation and mitigate potential shortcomings. To address this gap, this case study is conducted to describe factors contributing to teachers’ demotivation and the strategies teachers employ to maintain their motivation. Semi-structured interviews were used to gather data from two EFL teachers voluntarily involved in this study. Using thematic analysis, this study elucidated that EFL teachers employ several motivational strategies such as spiritual and social strategies, engaging in pleasure activities, participating in professional development, and seeking help from peers to tackle demotivational conditions in their schools. Discussion, limitations, and significance of this study will be further discussed.